The infarct‐limiting effect of cerebral ischaemic postconditioning in rats depends on the middle cerebral artery branching pattern. Issue 1 (30th November 2012) - Shcherbak, Natalia; Popovetsky, Maxim; Galagudza, Michael; Barantsevitch, Eugene; Shlyakhto, Eugene
Summary: Cerebral ischaemic postconditioning (PostCon) is a recently discovered endogenous neuroprotective phenomenon that occurs after several brief bouts of reperfusion/ischaemia instituted immediately after prolonged cerebral ischaemia. Data on the extent of PostCon‐mediated infarct size limitation in models of focal cerebral ischaemia–reperfusion are controversial. In this study, we investigated the infarct‐limiting effect of PostCon in the rat model of focal cerebral ischaemia–reperfusion. The relationship between anatomic pattern of the middle cerebral artery (MCA) and infarct size was also studied. The protocol of PostCon consisting of five episodes each of 10‐s ischaemia and 10‐s reperfusion was protective in terms of infarct size limitation only in animals with the typical bifurcating MCA branching pattern. The anatomic pattern of the MCA should be considered as one of the important factors influencing the outcome of neuroprotection studies.